Program Makan Bergizi Gratis: Analisis Kritis Transformasi Pendidikan Indonesia Menuju Generasi Emas 2045 - Albaburrahim, Albaburrahim; Putikadyanto, Agus Purnomo Ahmad; Efendi, Agik Nur; Alatas, Mochamad Arifin; Romadhon, Sahrul; Wachidah, Liana Rochmatul (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
This research analyzes the Free Nutritious Meal Program (MBG) which is one of Prabowo Subianto’s programs as a strategic effort to accelerate the transformation of Indonesian education to achieve the vision of the Golden Generation 2045. This research used a qualitative approach with a case study design. Data were collected through interviews with principals, parents, teachers, and students in schools that received the program. Analysis of policy documents and evaluation reports, as well as direct observation of program implementation, were used to gain a thorough understanding. This research shows that the program can generally improve health, academic achievement, and the golden generation of 2045. However, there are various challenges to the program, namely: First, the distribution of logistics in remote areas. Secondly, the lack of health standardization, sustainable financing, and changes in the behavior of the Indonesian people.